Simulating rotationally inelastic collisions using a direct simulation Monte Carlo method - Rennick, C; Schullian, O; Loreau, J; Vaeck, N; van der Avoird, A; Heazlewood, B; Softley, T (University of Oxford, 2015)
Cross sections for He NH3 rotationally inelastic collisions in text file format. Results from a direct simulation Monte Carlo simulation of a supersonic expansion in HDF5 format. Python scripts to generate paper figures from simulation results. A new approach to simulating rotational cooling using a Direct Simulation Monte Carlo (DSMC) method is described and applied to the rotational cooling of ammonia seeded into a helium supersonic jet. The method makes use of {\it ab initio} rotational state changing cross sections calculated as a function of collision energy. Each particle in the DSMC simulations is labelled with a vector of rotational populations that evolves with time. Transfer of energy into translation is calculated from the mean energy transfer for this population at the specified collision energy. The simulations are compared with a continuum model for the on-axis density, temperature and velocity; rotational temperature as a function of distance from the nozzle is in accord with expectations from experimental measurements. The method could be applied to other types of gas mixture dynamics under non-uniform conditions, such as buffer gas cooling of NH$_3$ by He.